12 things to know about the Bronze Age - Marquardt, Meg (Marquardt, Meg. Prehistoric., 2020)
Describes twelve aspects of the Bronze Age, including the origins of using metal tools, and explains how this innovation led to the development of larger civilizations, advanced religious practices, wider regional trade, and the development of language. Includes illustrations, a timeline, a glossary, and resources for further information.